5PSQ-143 Drug resistant tuberculosis in a high complexity specialised unit: epidemiology, treatment and main adverse reactions. (14th March 2021) - Ayllón, M; Sobrino, C; Bilbao, C; García-Trevijano, M; Escario, M; Arancón, AB; Jimenez, C; Álvarez, J; Herrero, A
Abstract : Background and importance: Inadequate therapeutic regimens and lack of adherence due to adverse effects of antituberculosis drugs have made resistance to these drugs a major public health problem. A better understanding of these issues may lead to better outcomes. Aim and objectives: To describe the population with drug resistant tuberculosis, the most used treatments, their adverse drug reactions (ADR) and their efficacy. Material and methods: A descriptive, observational, retrospective study was carried out. All patients cared for in our hospital that finished their treatments for drug resistant Mycobacterium tuberculosis between 2015 and 2019 were included. Results: 13 patients were analysed (62% men, mean age 43 (SD 14.8) years). Patients came from the following places: 46% Eastern Europe, 38% Latin America, 8% Western Europe and 8% Asia. Nine patients were diagnosed with multidrug resistant tuberculosis, 2 with polyresistant tuberculosis and 2 with extensive drug resistant tuberculosis. The therapies included 6–9 different antituberculosis drugs. The most commonly used were linezolid and moxifloxacin (13/13), followed by amikacin and clofazimine (12/13). Other prescribed drugs were cycloserine (10/13), prothionamide (10/13), pyrazinamide (5/13), ethambutol (5/13), isoniazid (3/13), bedaquiline (2/13), meropenem/clavulanate (2/13), streptomycin (1/13), rifampicin (1/13) and rifabutin (1/13). All patients had some ADR. The most frequent ADR were neurological (10), gastrointestinal (9), ototoxicity (5) and hepatitis (4). Cycloserine caused ADR (psychological, dizziness) in 70% of patients; amikacin (ototoxicity), ethambutol (cutaneous, neurological) and pyrazinamide (hyperuricaemia, arthralgia) in 40%; clofazimine (cutaneous, gastrointestinal), linezolid (neurological, aplasia) and prothionamide (gastrointestinal, hormonal) in 30%; moxifloxacin (fasciitis, nausea) in 8%. All patients reached seroconversion after 1.9 (SD 0.77) months from the beginning of treatment. Conclusion and relevance: Most of the patients diagnosed with drug resistant tuberculosis came from Eastern Europe and Latin America. Moxifloxacin and linezolid were the most used drugs. Cycloserine was the most toxic treatment. Despite the high frequency of ADR reported, all treatments were effective. References and/or acknowledgements: Conflict of interest: No conflict of interest